2015
DOI: 10.1016/j.bbi.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of NOD1 or NOD2 and TLR4 activation on mouse sickness behavior in relation to immune and brain activity markers

Abstract: Toll-like receptors (TLRs) and nuclear-binding domain (NOD)-like receptors (NLRs) are sensors of bacterial cell wall components to trigger an immune response. The TLR4 agonist lipopolysaccharide (LPS) is a strong immune activator leading to sickness and depressed mood. NOD agonists are less active but can prime immune cells to augment LPS-induced cytokine production. Since the impact of NOD and TLR co-activation in vivo has been little studied, the effects of the NOD1 agonist FK565 and the NOD2 agonist muramyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 76 publications
6
60
0
1
Order By: Relevance
“…Highlighting this novel role, mice deficient in Nod1/2 subjected to WAS had pronounced cognitive dysfunction, as well as anxiety-like and depressive-like behaviors, compared to WT(+WAS) controls. These findings complement previous studies by Farzi et al , who showed a role for NLR in regulating sickness behaviors (47). In contrast to these previous findings, however, exposure to an acute stressor was necessary to uncover behavioral deficits in NodDKO mice, suggesting a different mechanism of action is involved in the response to immune stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Highlighting this novel role, mice deficient in Nod1/2 subjected to WAS had pronounced cognitive dysfunction, as well as anxiety-like and depressive-like behaviors, compared to WT(+WAS) controls. These findings complement previous studies by Farzi et al , who showed a role for NLR in regulating sickness behaviors (47). In contrast to these previous findings, however, exposure to an acute stressor was necessary to uncover behavioral deficits in NodDKO mice, suggesting a different mechanism of action is involved in the response to immune stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…An open field test with healthy C57BL/6N mice was carried out as previously described. 31 The experimental procedures were approved by the Austrian Federal Ministry of Science, Research and Economy (BMWF-66.010/0037-II/3b/2013). Briefly, mice received 20 mg/kg CID16020046 (or DMSO as vehicle) daily over a period of 6 days.…”
Section: Open Field Testmentioning
confidence: 99%
“…C57BL/6 mice were treated with an intraperitoneal injection of 0.83 mg/kg LPS (Farzi et al 2015) (Sigma, Vienna, Austria) or with PBS alone (vehicle) and killed 4 h later.…”
Section: Methodsmentioning
confidence: 99%